Review of “Wikinomics“ (Don Tapscott & Anthony D. Williams) - Fuchs, Christian (Politics and Culture)

Deconstructive Class Analysis: Theoretical Foundations and Empirical Examples for the Analysis of Richness and the Class Analysis of the Media and the Culture Industry. ICT&S Research Paper No. 4 - Fuchs, Christian

Critical evaluation of the state of iron oxide nanoparticles on different mesoporous silicas prepared by an impregnation method - Tsoncheva, Tanya; Rosenholm, Jessica; Linden, Mika; Kleitz, Freddy; Tiemann, Michael; Ivanova, Ljubomira; Dimitrov, Momtchil; Paneva, Daniela; Mitov, Ivan; Minchev, Christo (Microporous and Mesoporous Materials)
Mesoporous SBA-15 (space group p6mm), KIT-6 (Ia3d) and KIT-5 (Fm3m) silicas, exhibiting different 2-D and 3-D channel- or cage-like pore structure and pore dimensions have been used as supports for iron oxide nanoparticles. The iron modification of the silica was performed according to a frequently used impregnation technique from aqueous iron nitrate solution. The materials were characterized by nitrogen physisorption, X-ray diffraction, TEM–EDX, Moessbauer spectroscopy, and temperature-programmed reduction (TPR) and tested in the catalytic decomposition of methanol. It is established that the location and dispersion of iron oxide nanoparticles are affected by the pore topology of the support. The most homogeneously dispersed iron oxide nanoparticles are observed using silica host matrix exhibiting a 3-D channel-like structure and pore diameters about 7 nm, and the thus-obtained composites exhibit high catalytic activity and selectivity in methanol decomposition to CO and hydrogen. For all the samples, characterized with a low mesopore volume and small pore diameters/pore entrances, the formation of larger iron oxide particles, mainly located on the outer surface, is observed. Inhomogeneously dispersed iron oxide particles with a large fraction of isolated, strongly interacting with the support, iron species, and possessing low catalytic activity and usually high selectivity to methane, are found for the silicas with relatively larger pores/pore entrances.

Synthesis of mesoporous metal oxides by structure replication: Strategies of impregnating porous matrices with metal salts - Roggenbuck, Jan; Waitz, Thomas; Tiemann, Michael (Microporous and Mesoporous Materials)
Various measures to optimise the impregnation of mesoporous CMK-3 carbon and SBA-15 silica matrices with metal nitrates for the synthesis of mesoporous metal oxides by structure replication are investigated. The effect of surface modification of the matrix pores, the choice of a solvent with suitable polarity, and the concentration of the metal nitrate solution are studied in detail. The efficiency of pore loading is monitored by nitrogen physisorption measurements. The creation of polar functions at the pore surface of CMK-3 carbon is shown to increase the impregnation efficiency substantially while maximizing the pore wall polarity of SBA-15 silica by increasing the amount of free silanol groups does not have any significant impact. The choice of a less polar solvent (THF instead of water) has a positive effect on the wettability of CMK-3 carbon in the first impregnation cycle but turns out to be disadvantageous in the second cycle; a similar trend is observed for variation of the metal salt concentration.

Iron oxide nanoparticles supported on mesoporous MgO and CeO2: A comparative physicochemical and catalytic study - Tsoncheva, Tanya; Roggenbuck, Jan; Tiemann, Michael; Ivanova, Lyubomira; Paneva, Daniela; Mitov, Ivan; Minchev, Christo (Microporous and Mesoporous Materials)
Iron (III) containing nanoparticles with superparamagnetic behaviour are prepared via deposition on various mesoporous supports (MgO, CeO2 and SBA-15). XRD, TEM-EDX, N2 physisorption, FTIR, and Moessbauer spectroscopy are used for their characterization. The reductive properties and catalytic behaviour in methanol decomposition of the materials are also studied. Depending on the chemical nature of the support, the predominant formation of: isolated iron species, strongly interacting with the support (for SBA-15), mixture of hematite and binary MgFe2O4 nanoparticles (for MgO) or almost homogeneously dispersed hematite particles (for CeO2) are observed. The state of iron species strongly affects their catalytic properties. The favorable effect of the support mesoporosity on the catalytic activity is most pronounced for the iron modified CeO2.

New mesoporous metal oxides as gas sensors - Waitz, Thomas; Wagner, Thorsten; Kohl, Claus-Dieter; Tiemann, Michael (Zeolites and related materials: Trends, targets and challenges, Proceedings of the 4th International FEZA Conference)
Nanoporous semiconducting metal oxide materials (In2O3, WO3) with uniform pore systems, large specific surface areas (80 m2 g−1), and pore-wall crystallinity were prepared by structure replication, using KIT-6 silica as a template. The products show improved properties as gas sensors (for methane or butanone) as compared to non-porous samples. In addition, porous WO3 samples with comparable porosity (prepared by conventional ‘soft templating’, using pluronic P123), which are amorphous on the atomic length scale show poorer gas sensitivity, indicating that crystallinity is a crucial factor in the sensing process.

Ripening Effects in ZnS Nanoparticle Growth - Tiemann, Michael; Marlow, Frank; Hartikainen, Juha; Weiss, Özlem; Lindén, Mika (The Journal of Physical Chemistry C)
The growth of ZnS nanoparticles during precipitation from aqueous solution is studied by in situ stopped-flow UV absorption spectroscopy at temperatures between 283 and 323 K. Particle growth is marked by substantial ripening during the first 60 ms. Kinetic data suggest that a ripening mechanism by coalescence (oriented attachment) is predominant over Ostwald ripening, although the latter seems to coexist to a significant degree at early temporal stages, predominantly at low temperatures.

Repeated Templating - Tiemann, Michael (Chemistry of Materials)
In recent years, a lot of research activity has focused on the synthesis of new ordered porous materials by utilization of porous matrices as templates. Since the matrices are themselves created by templating procedures, the entire process can be envisaged as “repeated templating”. This review describes recent conceptual developments in the field of structure replication and summarizes the large number of publications on new functional materials prepared by this method.

Mesoporous Ceria by Structure Replication from Various Porous Matrices - ROGGENBUCK, JAN; Tiemann, Michael (Nanoporous Materials)
Mesoporous ceria was synthesized by using both CMK-3 carbon and SBA-15 silica as structure matrices. All products exhibit uniform mesopores with diameters of 5-6 nm in a two-dimensional periodic arrangement in addition to varying amounts of interparticle porosity. The gas sensing properties (methane detection) of ordered mesoporous ceria was compared to a non-porous sample.

Power management for thermal energy harvesting in aircrafts - Becker, Th.; Kluge, M.; Schalk, J.; Otterpohl, T.; Hilleringmann, Ulrich (2008 IEEE Sensors)